High-breathability carbon nitride diaphragm as well as preparation method and application thereof

By performing bidirectional stretching of the base film on the carbon nitride separator, the problems of poor gas permeability and poor electrolyte wetting are solved, and the performance of lithium-ion batteries is significantly improved.

CN119674429APending Publication Date: 2025-03-21上海科源固能新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators based on carbon nitride have problems such as poor breathability and poor electrolyte wetting, which leads to poor battery performance.

Method used

By bidirectional stretching of the base film, the surface of carbon nitride is cracked, and the porosity of the base film is increased, thereby improving the breathability of the separator.

Benefits of technology

The breathability of the carbon nitride separator and the wetting properties of the electrolyte are significantly improved, and the performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674429A_ABST
    Figure CN119674429A_ABST
Patent Text Reader

Abstract

The invention relates to a high-permeability carbon nitride diaphragm as well as a preparation method and application thereof. Preparing carbon nitride slurry, adding a dispersing agent, and stirring and dispersing; coating the surface of the diaphragm with the prepared carbon nitride slurry by using a bar coating machine, and then drying to obtain a carbon nitride diaphragm; carrying out two-way stretching treatment on the prepared carbon nitride diaphragm; and carrying out two-way stretching on the carbon nitride diaphragm by using a two-way stretching machine to obtain the high-permeability carbon nitride diaphragm. Compared with the prior art, the invention provides a method for biaxially stretching the base membrane, so that the carbon nitride on the surface is cracked, the pores of the base membrane are further enlarged, the problem of pore blockage of the carbon nitride diaphragm is solved, and a foundation is laid for industrialization of the carbon nitride diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy material preparation, and in particular relates to a highly air-permeable carbon nitride diaphragm and a preparation method and application thereof. Background Art

[0002] Among the various materials that make up the battery, the separator is the most important component to prevent the battery from short circuiting. At the same time, it also provides a path for the movement of lithium ions between the positive and negative electrodes. With the continuous advancement of science and technology, higher and higher requirements are placed on the safety, energy density, and electrochemical performance of lithium-ion batteries.

[0003] Since the diaphragm is directly related to the electrochemical properties of lithium-ion batteries, lithium-ion batteries with high safety, high energy density and good electrochemical performance also place many high demands on the related properties of the diaphragm.

[0004] At present, most commercial diaphragms are microporous polyolefin diaphragms mainly based on polyethylene (PE) and polypropylene (PP), with nanometer-level pore size and high porosity. However, polyolefin diaphragms have poor wettability and poor liquid retention, which affects the ionic conductivity, cycle performance, and rate performance of lithium-ion batteries. In addition, the energy density requirements for lithium-ion batteries are getting higher and higher at this stage, which requires the diaphragm to be thinner and have better liquid retention, mechanical strength and heat resistance to meet the safety performance of the battery. Therefore, there is an urgent need to develop a diaphragm with excellent comprehensive performance to meet the demand.

[0005] At present, there are some lithium-ion battery separators based on carbon nitride. The surface of carbon nitride has a considerable number of active groups and good heat resistance. The separator coated with carbon nitride can improve the rate performance and safety performance of the battery. However, due to the flaky structure of carbon nitride, the pores of the carbon nitride separator are blocked, resulting in poor air permeability of the separator and poor electrolyte wettability, thus deteriorating the battery performance. Summary of the invention

[0006] In order to solve the problems of poor membrane permeability and poor electrolyte wettability in the prior art carbon nitride-based lithium ion battery membrane, the present invention provides a highly permeable carbon nitride membrane and a preparation method and application thereof.

[0007] The present invention uses a method of biaxially stretching the base film to crack the carbon nitride on the surface, thereby further enlarging the pores of the base film, thereby solving the problem of pore blocking of the carbon nitride diaphragm.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] The present invention provides a method for preparing a highly permeable carbon nitride diaphragm, comprising the following steps:

[0010] 1) preparing carbon nitride slurry, adding dispersant, and stirring and dispersing;

[0011] 2) applying the prepared carbon nitride slurry on the surface of the diaphragm using a wire rod coater, and then drying to obtain a carbon nitride diaphragm;

[0012] 3) Biaxially stretching the prepared carbon nitride membrane: biaxially stretching the carbon nitride membrane using a biaxial stretching machine to obtain a highly air-permeable carbon nitride membrane.

[0013] In one embodiment of the present invention, in step 1), the solid content of carbon nitride in the carbon nitride slurry is 0.05-2 wt%, preferably 1 wt%.

[0014] In one embodiment of the present invention, in step 1), the carbon nitride can also be replaced by other sheet materials, such as boron nitride, graphene, carbon nitride, black phosphorene, etc., and the solid content thereof is 0.05 to 2 wt%.

[0015] In one embodiment of the present invention, in step 1), the dispersant is one or a combination of polyvinyl pyrrolidone, sodium hexametaphosphate, sodium polyphosphate, sodium polyacrylate, carboxymethyl cellulose or sodium stearate, preferably polyvinyl pyrrolidone.

[0016] In one embodiment of the present invention, in step 1), the amount of the dispersant added is 0.1 wt% to 1 wt%, preferably 0.3 wt%.

[0017] In one embodiment of the present invention, in step 1), stirring is performed using a stirrer.

[0018] In one embodiment of the present invention, in step 1), the linear speed of stirring the carbon nitride slurry is 1 to 6 m / s, preferably 3 m / s.

[0019] In one embodiment of the present invention, in step 2), the coating speed of the wire rod coater is 5 to 60 mm / s, and the wire rod mesh number is 50 to 300 meshes.

[0020] In one embodiment of the present invention, in step 2), preferably, the coating speed of the wire rod coater is 20 mm / s, and the wire rod mesh number is 150 meshes.

[0021] In one embodiment of the present invention, in step 2), the thickness of the carbon nitride membrane is between 5 and 30 um, and preferably, the thickness of the carbon nitride membrane is 9 um.

[0022] In one embodiment of the present invention, in step 2), an oven is used for drying.

[0023] In one embodiment of the present invention, in step 2), the drying temperature is 40-120° C., and the heat preservation time is 5-30 minutes. Preferably, the drying temperature is 70° C., and the heat preservation time is 10 minutes.

[0024] In one embodiment of the present invention, in step 3), when a biaxial stretching machine is used to biaxially stretch the carbon nitride membrane, the temperature of the biaxial stretching machine is first raised to a certain temperature, and then the carbon nitride membrane is placed. After keeping the temperature for a period of time, the carbon nitride membrane is synchronously biaxially stretched.

[0025] In one embodiment of the present invention, in step 3), the temperature of the biaxial stretching machine is controlled at 80-120°C, and the holding time is 5-20 minutes. Preferably, the temperature of the biaxial stretching machine is controlled at 100°C, the holding time is 10 minutes, and the stretching speed is 5 mm / min.

[0026] In one embodiment of the present invention, in step 3), the area of ​​the highly permeable carbon nitride membrane after stretching is 1.1 to 1.5 times the area of ​​the carbon nitride membrane before stretching. Preferably, the area of ​​the highly permeable carbon nitride membrane after stretching is 1.2 times the area of ​​the carbon nitride membrane before stretching.

[0027] The present invention further provides a highly permeable carbon nitride diaphragm obtained based on the above preparation method.

[0028] The present invention further provides an application of a highly air-permeable carbon nitride diaphragm obtained based on the above preparation method in the preparation of a lithium-ion battery.

[0029] The present invention further provides a lithium ion battery comprising the above-mentioned highly permeable carbon nitride diaphragm.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] The surface of carbon nitride has a considerable number of active groups and good heat resistance. The diaphragm coated with carbon nitride can improve the rate performance and safety performance of the battery cell. However, due to the flaky structure of carbon nitride, the pores of the carbon nitride diaphragm are blocked, resulting in poor air permeability of the diaphragm and poor electrolyte wettability, thereby deteriorating the battery performance. In order to solve this problem, the present invention provides a method of biaxially stretching the base film to crack the carbon nitride on the surface and further enlarge the pores of the base film to solve the problem of pore blocking of the carbon nitride diaphragm, laying a foundation for the industrialization of the carbon nitride diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : SEM images of the carbon nitride membrane surfaces before and after being stretched 1.2 times in Comparative Example 1 and Example 1;

[0033] Figure 2: Comparison of ion migration numbers of carbon nitride diaphragm batteries before and after stretching 1.2 times between Comparative Example 1 and Example 1;

[0034] Figure 3 : Comparison of ionic conductivity of carbon nitride separator battery before and after stretching 1.2 times between Comparative Example 1 and Example 1;

[0035] Figure 4 : Comparison of the rate performance of the carbon nitride diaphragm graphite semi-electric before and after stretching 1.2 times between Comparative Example 1 and Example 1;

[0036] Figure 5 : Comparison of thermal shrinkage of the highly air-permeable carbon nitride diaphragm and the base film between Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] Example 1

[0039] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The line speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 100°C, then place the carbon nitride diaphragm, and after a 10min insulation period, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.2 times the original carbon nitride area. Finally, a highly breathable carbon nitride diaphragm is obtained.

[0040] Example 2

[0041] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The linear speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 300 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 100°C, then place the carbon nitride diaphragm, and after a 10min insulation period, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.2 times the original carbon nitride area. Finally, a highly breathable carbon nitride diaphragm is obtained.

[0042] Example 3

[0043] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The linear speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 100°C, then place the carbon nitride diaphragm, and after a 10min insulation period, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.1 times the original carbon nitride area. Finally, a highly breathable carbon nitride diaphragm is obtained.

[0044] Example 4

[0045] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The linear speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 100°C, then place the carbon nitride diaphragm, and after a 10min insulation period, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.5 times the original carbon nitride area. Finally, a highly breathable carbon nitride diaphragm is obtained.

[0046] Example 5

[0047] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The line speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 120°C, then place the carbon nitride diaphragm, and after a 10min insulation period, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.2 times the original carbon nitride area. Finally, a highly breathable carbon nitride diaphragm is obtained.

[0048] Comparative Example 1

[0049] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer to stir and disperse. The line speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at 70°C for 10min.

[0050] Comparative Example 2

[0051] Prepare a carbon nitride slurry with a solid content of 0.5wt% and add 0.3wt% of dispersant PVP, and use a stirrer to stir and disperse. The linear speed of the stirrer is 3m / s and the stirring is for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at 70°C for 10min.

[0052] Comparative Example 3

[0053] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The linear speed of the stirrer is 3m / s and the stirring is performed for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C for 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 130°C, then place the carbon nitride diaphragm, and after keeping warm for 10min, perform synchronous biaxial stretching on the carbon nitride diaphragm. The area of ​​biaxial stretching is 1.6 times the original carbon nitride area. The carbon nitride diaphragm breaks.

[0054] Comparative Example 4

[0055] Prepare a carbon nitride slurry with a solid content of 1wt% and add 0.3wt% of dispersant PVP, and use a stirrer for stirring and dispersion. The linear speed of the stirrer is 3m / s and the stirring is performed for 2h. Then use the prepared carbon nitride diaphragm slurry for coating. The coating speed of the wire rod coater is 20mm / s, and the mesh number of the wire rod is 150 mesh. Put the coated carbon nitride diaphragm into an oven for drying at a temperature of 70°C and a heat preservation time of 10min. Put the dried diaphragm into a biaxial stretching machine for stretching. First, raise the temperature of the biaxial stretching machine to 120°C, then place the carbon nitride diaphragm, and after keeping warm for 10min, the carbon nitride diaphragm is synchronously biaxially stretched. The area of ​​biaxial stretching is 1.6 times the original carbon nitride area. The carbon nitride diaphragm breaks.

[0056] The thermal shrinkage and air permeability of the carbon nitride diaphragms obtained in the above embodiments and comparative examples are shown in Table 1 and Figure 1-5 shown.

[0057] Table 1 Thermal shrinkage and air permeability of carbon nitride membranes obtained in various examples and comparative examples

[0058]

[0059] As can be seen from Table 1, by comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the biaxial stretching process can significantly improve the air permeability of the carbon nitride diaphragm. By comparing Example 1 with Example 2, it can be seen that the heat shrinkage and air permeability of the carbon nitride diaphragm are changed by using wire rods with different mesh sizes. The higher the mesh size, the better the heat shrinkage and the worse the air permeability. By comparing Example 1 with Example 3, it can be seen that the smaller the biaxial stretching area, the worse the air permeability.

[0060] from Figure 1 It can be seen that the carbon nitride membranes prepared in Comparative Example 1 and Example 2 were characterized by SEM, and it can be seen that the carbon nitride membranes after biaxial stretching have obvious gaps, which improves the air permeability of the membranes.

[0061] from Figure 2 It can be seen that the carbon nitride membranes prepared in Comparative Example 1 and Example 2 were respectively assembled into Li-carbon nitride membrane-stainless steel batteries, and the ion migration number test was carried out. It can be seen that the ion migration number of the carbon nitride membrane after biaxial stretching is significantly higher than that of the unstretched carbon nitride membrane, which is more conducive to lithium ion transmission.

[0062] from Figure 3 It can be seen that the carbon nitride membranes prepared in Comparative Example 1 and Example 2 were respectively assembled into stainless steel-carbon nitride membrane-stainless steel symmetrical batteries, and the ion conductivity test was carried out. It can be seen that the ion conductivity of the carbon nitride membrane after biaxial stretching is significantly higher than that of the unstretched carbon nitride membrane, and the lithium ion transmission is faster.

[0063] from Figure 4 It can be seen that the carbon nitride membranes prepared in Comparative Example 1 and Example 2 were respectively assembled into Li-carbon nitride membrane-positive electrode batteries, and battery rate tests were carried out. The rates were from low to high, ranging from 0.1C-0.2C-0.5C-1C-2C-3C-5C. It can be seen that the battery rate performance assembled with the carbon nitride membrane after biaxial stretching is better.

[0064] from Figure 5 It can be seen that the carbon nitride diaphragms prepared in Comparative Example 1 and Example 2 were placed in an oven and baked at 130°C for 1 hour. It can be seen that the carbon nitride diaphragms after biaxial stretching had no obvious shrinkage, indicating that the diaphragms have better thermal shrinkage performance and better safety performance.

[0065] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a highly permeable carbon nitride membrane, characterized in that: The following steps are involved: 1) preparing carbon nitride slurry, adding dispersant, and stirring and dispersing; 2) applying the prepared carbon nitride slurry on the surface of the diaphragm using a wire rod coater, and then drying to obtain a carbon nitride diaphragm; 3) Biaxially stretching the prepared carbon nitride membrane: biaxially stretching the carbon nitride membrane using a biaxial stretching machine to obtain a highly air-permeable carbon nitride membrane.

2. The method for preparing a highly permeable carbon nitride membrane according to claim 1, characterized in that: In step 1), the solid content of carbon nitride in the carbon nitride slurry is 0.05 to 2 wt%; In step 1), the dispersant is one or a combination of polyvinyl pyrrolidone, sodium hexametaphosphate, sodium polyphosphate, sodium polyacrylate, carboxymethyl cellulose or sodium stearate; In step 1), the amount of the dispersant added is 0.1wt% to 1wt%; In step 1), the linear speed of stirring the carbon nitride slurry is 1 to 6 m / s.

3. The method for preparing a highly permeable carbon nitride membrane according to claim 2, characterized in that: In step 1), the solid content of carbon nitride in the carbon nitride slurry is 1 wt%; The dispersant is polyvinyl pyrrolidone, and the added amount of the dispersant is 0.3wt%; In step 1), the linear velocity of stirring the carbon nitride slurry is 3 m / s.

4. The method for preparing a highly permeable carbon nitride membrane according to claim 1, characterized in that: In step 2), the coating speed of the wire rod coater is 5 to 60 mm / s, and the wire rod mesh number is 50 to 300 meshes; The thickness of the carbon nitride diaphragm is between 5 and 30 um; The drying temperature is 40-120°C and the insulation time is 5-30 minutes.

5. The method for preparing a highly permeable carbon nitride membrane according to claim 4, characterized in that: In step 2), the coating speed of the wire rod coater is 20 mm / s, and the wire rod mesh number is 150 mesh; The thickness of the carbon nitride diaphragm is 9um; The drying temperature is 70°C and the holding time is 10 minutes.

6. The method for preparing a highly permeable carbon nitride membrane according to claim 1, characterized in that: In step 3), the temperature of the bidirectional stretching machine is controlled at 80-120° C., and the insulation time is 5-20 min; In step 3), the area of ​​the highly air-permeable carbon nitride membrane after stretching is 1.1 to 1.5 times the area of ​​the carbon nitride membrane before stretching.

7. The method for preparing a highly permeable carbon nitride membrane according to claim 6, characterized in that: In step 3), the temperature of the bidirectional stretching machine is controlled at 100°C and the holding time is 10 minutes; The area of ​​the highly permeable carbon nitride membrane after stretching is 1.2 times the area of ​​the carbon nitride membrane before stretching.

8. A highly permeable carbon nitride membrane obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the highly permeable carbon nitride membrane as claimed in claim 8 in the preparation of lithium-ion batteries.

10. A lithium ion battery, characterized in that: A highly gas-permeable carbon nitride membrane comprising the method of claim 8.